The Effect of Exhaustion, Depersonalization, and Personal Achievement Variables Towards Job Performance - Naomi Putri Hudiana; Martinus Thjia Tjen Jong (Enrichment : Journal of Management, 2021)
This study aims to see the effect of exhaustion, depersonalization and personal achievement variables towards job performance among nurses at the Condong Catur Hospital in Sleman, Yogyakarta. The survey method used in this research is by distributing questionnaires. The research subject in this study is a total of 58 nurses at the Condong Catur Hospital. Data analysis was carried out using the PLS-SEM approach through the SmartPls program. The results obtained indicate that there is a negative effect of exhaustion on nurse performance and the hypothesis is supported. There is a negative effect of depersonalization on nurse performance and the hypothesis is supported. There is a negative effect of personal achievement on nurse performance and the hypothesis is not supported.